Protective effects of natural and partially degraded konjac glucomannan on Bifidobacteria against antibiotic damage. (1st February 2018) - Mao, Yu-Heng; Song, Ang-Xin; Yao, Zhong-Ping; Wu, Jian-Yong
Highlights: Konjac glucomannan (KGM) were partially degraded by ultrasound and further by acid. Native and degraded KGM were applied to bifidobacterial cultures exposed to antibiotics. US-degraded KGM most effectively protected Bifidobacteria against antibiotic inhibition. The protection was attributable to adsorption of antibiotics and formation of biofilm. Abstract: This study was to evaluate the protective effects of a dietary fiber, konjac glucomannan (KGM) from the plant tuber of Amorphohallus konjac on Bifidobacteria against antibiotic damage. KGM (∼8.8 × 10 8  Da) was partially degraded with high-intensity ultrasound to KGM-US (∼1.8 × 10 6  Da) and then hydrolyzed with trifluoroacetic acid (TFA) to KGM-AH (1369 Da). KGM-US (at 5 g/l) showed the most significant protective effect on most bifidobacterial strains against penicillin and streptomycin inhibition, increasing the minimal inhibitory and bactericidal concentration (MIC and MBC) dramatically, and KGM also showed significant effects on enhancing the MBC of enrofloxacin, penicillin, tetracycline and streptomycin. In addition, the adsorbance ability and biofilm formation effects of KGM and degraded KGM products may be partially responsible for the protective effects. The results suggested that natural KGM and ultrasound treated KGM have protective effects for the human gut probiotic bacteria against the damage caused by specific antibiotics.